2000
DOI: 10.1523/jneurosci.20-21-08153.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β-Induced Changes in Blood–Brain Barrier Permeability, Apparent Diffusion Coefficient, and Cerebral Blood Volume in the Rat Brain: A Magnetic Resonance Study

Abstract: The cytokine interleukin-1␤ (IL-1␤) is implicated in a broad spectrum of CNS pathologies, in which it is thought to exacerbate neuronal loss. Here, the effects of injecting recombinant rat IL-1␤ into the striatum of 3-week-old rats were followed noninvasively from 2 to 123 hr using magnetic resonance imaging and spectroscopy. Four hours after injection of IL-1␤ (1 ng in 1 l), cerebral blood volume was significantly increased, the blood-brain barrier (BBB) became permeable to intravenously administered contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
150
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(161 citation statements)
references
References 56 publications
8
150
3
Order By: Relevance
“…The mechanism underlying the increase in rCBV is unclear but may reflect, at least in part, (1) reactivation of metabolically active leukocytes, (2) local produc- tion of the vasodilator nitric oxide (Willenborg et al, 1999), or (3) increased expression of local cytokines. We have shown previously that injection of IL-1␤ into the rat brain results in an acute increase in rCBV (Blamire et al, 2000). It is also known that peripheral injection of LPS induces IL-1␤ expression in both the periphery and the brain (Zetterström et al, 1998;McColl et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism underlying the increase in rCBV is unclear but may reflect, at least in part, (1) reactivation of metabolically active leukocytes, (2) local produc- tion of the vasodilator nitric oxide (Willenborg et al, 1999), or (3) increased expression of local cytokines. We have shown previously that injection of IL-1␤ into the rat brain results in an acute increase in rCBV (Blamire et al, 2000). It is also known that peripheral injection of LPS induces IL-1␤ expression in both the periphery and the brain (Zetterström et al, 1998;McColl et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Besides MCP1, many other cytokines, including interleukin (IL)-1, IL-4, IL-8, IL-10, IL-13, tumor necrosis factor (TNF)-a and interferon (IFN)- (Ahdieh et al, 2001;Blamire et al, 2000;Coyne et al, 2002;Paul et al, 2003;Ross and Joyner, 1997;Wojciak-Stothard et al, 1998;Yang et al, 1999;Youakim and Ahdieh, 1999), have been shown to change the structure of tight junctions and promote the formation of stress fibers in epithelial and endothelial cells. Whether these molecules induce BBB compromise using the same signaling pathways is not clear; however, on the basis of the conserved function and high expression level of ERM proteins in epithelial and endothelial cells, we would assume the same signaling pathways are activated upon the cytokine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To address the potential role of these inflammatory processes in the opening of the BBB (Blamire et al, 2000) we aimed to mimic the remote Gf accumulation after PT by systemic LPS application. Groups of three naive rats received LPS (0.5 mg/kg body weight) intraperitoneally and Gf 1 or 48 h thereafter i.v., and underwent MRI at 24 or 72 h, respectively.…”
Section: N -Methyl-d -Aspartate-receptor Blockage and Lipopolysaccharmentioning
confidence: 99%